FACTORS AFFECTING EFL STUDENTS MOTIVATION IN USING GOOGLE CLASSROOM AS AN ONLINE LEARNING PLATFORM - Lisma Sri Rahayu; Pipit Prihartanti Suharto; Sundari Purwaningsih (Universitas Perjuangan Tasikmalaya, 2021)
This research investigated factors affecting EFL students motivation when using Google Classroom as an online learning platform. It was argued that motivation is recognised as a vital component in successful second language learning (Lamb, 2017). This research employed survey method and data were obtained through the use of questionnaire with twenty questions for data collection. It involved fourteen students. The researcher was adapted to Rosnija, Chairunnisa and Apriliaswati (2017), to analyze the data from questionnaire. The finding revealed internal and external factors that affect students motivation in using Google Classroom as online learning platform. This paper concludes with internal factors such as easy to operate and help students for accessing new or old material. In the other hand, they lack communication and difficulty understanding the material so students feel that the learning is monotonous. Then, external factors such as bad networks, no phones or computer, limited quotas and no Wi-Fi so that students often miss material. Furthermore, no feedback from teachers, lack of disciplines among teachers in sharing materials and assignments, and no class discussion have affected students’ motivation in using Google Classroom. However, they still work on assignments because they have the purpose to get good grades, to be the champions of the class, and to avoid punishment at the end of the semester. Based on findings, it is recommended that teachers should pay attention to these factors so that students motivation in learning using Google Classroom increases better. Keywords: EFL students motivation; Google Classroom; internal factors; external factors